Introduction to Logic and Critical Thinking. - Salmon, Merrilee H. (New York Harcourt Brace Jovanovich, Publishers, 1984)
This book is designed to help the students who are beginning college to acquire a deeper understanding of the relationships between logic and language and to increase their skills in critical thinking.
Keywords: Psychology